Psychological Factors That Contribute to the Dearth of Black Students in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Efforts over the last several decades to increase the participation and leadership of Black men and women in the scientific and medical workforce have had limited results. Despite many individual successes, the number of Black professionals in science, engineering, and medicine (SEM) fields has not reached a level that corresponds with African American representation in the country at large. Structural racism affects progress at all stages along the pathway - from young children through graduate and medical students through faculty and clinicians at all levels. Beyond entry into educational programs or recruitment into workplaces seeking to diversify, challenges persist to achieve equity and inclusion for Black males and females. Moreover, psychological barriers confound the engagement of Black men and women in SEM fields. To explore these issues and suggest solutions, the National Academies of Sciences, Engineering, and Medicine launched the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine. Over the past 2 years, the Roundtable has convened workshops on K-12 education, the impact of COVID-19, financial burdens to pursuing SEM careers, and other topics. Sessions during each of these workshops identified psychological factors related to those specific topics. To have a more targeted discussion, the Roundtable convened a virtual workshop on September 14-15, 2021. As summarized in this proceedings, panelists and participants identified policies and practices that perpetuate these factors and explored solutions toward achieving and maintaining wellness, especially among students and young professionals.
Keywords: Education; Health and Medicine

Improving Diversity of the Genomics Workforce: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In 2020, as part of its strategic planning initiative, the Roundtable on Genomics and Precision Health of the National Academies of Sciences, Engineering, and Medicine decided to explore four action-oriented focus areas for its activities over the coming three to five years: driving innovation, shaping the policy dialogue, spurring the adoption of tools and approaches, and achieving equity. The roundtable began its exploration of the fourth thematic area - achieving equity in genomics and precision health - by holding a public workshop on October 5, 2021. The workshop, Improving Diversity of the Genomics Workforce, examined the current state of diversity of the genetics and genomics workforce; the structural and social factors associated with the lack of workforce diversity; the impact of diversity in the workforce on access to genetic services and patient outcomes; and possible actions that could lead to a more diverse, equitable, and inclusive genomics workforce. This Proceedings of a Workshop-in Brief highlights the presentations and discussions that occurred during the workshop.
Keywords: Health and Medicine

Understanding and Offsetting Financial Barriers for Black Students in Science, Engineering, and Medicine: Programs, Partnerships, and Pathways: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The number of Black students in science, engineering, and medicine in the United States has remained disproportionately low over the past several decades. A number of reasons have been identified as contributing to these low numbers, including those related to finances. Financial considerations range from the most immediate - the ability of students to pay for their education and associated costs - to more structural concerns, such as inequities that created and have perpetuated a wealth gap between races and ethnic groups. On April 19-20, 2021, the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine organized a virtual public workshop to examine financial barriers for Black students in science, engineering, and medicine, explore existing educational programs to them, and engage stakeholders in conversations about partnerships and policies that span academia, industry, and philanthropy. This publication summarizes the presentation and discussion of the workshop.
Keywords: Education

An American Crisis: The Growing Absence of Black Men in Medicine and Science: Proceedings of a Joint Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Black men are increasingly underrepresented in medical schools and in the medical profession. A diverse workforce is a key attribute of quality healthcare and research suggests that a diverse workforce may help to advance cultural competency and increase access to high-quality health care, especially for underserved populations. Conversely, lack of diversity in the health workforce threatens health care quality and access and contributes to health disparities. In this way, the growing absence of Black men in medicine is especially troubling, because their absence in medicine may have adverse consequences for health care access, quality, and outcomes among Black Americans and Americans overall. To better understand the factors that contribute to the low participation of Black men in the medical profession, facilitate discussion of current strategies used to increase their participation in medical education, and explore new strategies along the educational and professional pipeline that may have potential to increase participation in medicine, the National Academies of Sciences, Engineering, and Medicine and the Cobb Institute jointly convened a 2-day workshop in November 2017, in Washington, DC. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

COVID-19 and the Present and Future of Black Communities: The Role of Black Physicians, Engineers, and Scientists: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
While the COVID-19 pandemic has had devastating health and economic impacts in the United States, communities of color, especially Black communities, have been disproportionately affected. On June 23, 2020, the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop to discuss the landscape of COVID-19, including how systemic racism contributes to the disproportionate effects related to infection rates and mortality of this virus and other health conditions. Presenters highlighted relevant research and creative responses from many perspectives, including how Black scientists, engineers, and doctors are contributing to solutions and are ready to do more. National Academies leaders and members also discussed the role of the National Academies in addressing the pandemic and underlying issues of systemic racism that have led to health disparities in the United States. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Supporting Black Students Through Their Science, Engineering, and Medicine Career Journeys: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Increasing the number of Black men and Black women who enter the fields of science, engineering, and medicine (SEM) will benefit the social and economic health of the nation. On May 2-3, 2022 the Roundtable on Black Men and Black Women in Science, Engineering, and Medicine of the National Academies of Sciences, Engineering, and Medicine convened a workshop to highlight promising financial and supportive services and programs throughout various stages of career development. Sessions followed student progression through the major stages of education and career development, and identified policies and practices that aim to mitigate and alleviate long-standing barriers to the full participation of Black students in SEM at the K–12, undergraduate, and graduate and professional levels.
Keywords: Education

Educational Pathways for Black Students in Science, Engineering, and Medicine: Exploring Barriers and Possible Interventions: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Academic preparation is critical to increase Black representation in Science, Engineering, and Medicine, but so, too, are such interrelated factors as providing mentoring and role models in sufficient numbers, adequately funding school and community support services, and analyzing the intentional and unintentional consequences of a range of policies and practices. To address these issues, the Roundtable on Black Men and Black Women of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on September 2 and 3, 2020. Titled "Educational Pathways for Blacks in Science, Engineering, and Medicine: Exploring Barriers and Possible Interventions," the workshop provided a platform to explore challenges and opportunities, beginning in the earliest years of life through K-12 schooling, undergraduate and postgraduate education, and into the workforce. Presenters throughout the workshop provided perspectives from research and from their own experiences to discuss the need for systemic solutions inside and outside of formal education institutions. This publication summarizes the presentation and discussion of the workshop.
Keywords: Education

The Impacts of Racism and Bias on Black People Pursuing Careers in Science, Engineering, and Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Despite the changing demographics of the nation and a growing appreciation for diversity and inclusion as drivers of excellence in science, engineering, and medicine, Black Americans are severely underrepresented in these fields. Racism and bias are significant reasons for this disparity, with detrimental implications on individuals, health care organizations, and the nation as a whole. The Roundtable on Black Men and Black Women in Science, Engineering, and Medicine was launched at the National Academies of Sciences, Engineering, and Medicine in 2019 to identify key levers, drivers, and disruptors in government, industry, health care, and higher education where actions can have the most impact on increasing the participation of Black men and Black women in science, medicine, and engineering. On April 16, 2020, the Roundtable convened a workshop to explore the context for their work; to surface key issues and questions that the Roundtable should address in its initial phase; and to reach key stakeholders and constituents. This proceedings provides a record of the workshop.
Keywords: Behavioral and Social Sciences

Overcoming Structural Barriers for Women in Entrepreneurship: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
While there has been growth in the number of women entrepreneurs in the United States in recent years, the percentage of women - particularly women of color - who decide to pursue an entrepreneurial career continues to be significantly lower than that of men. Entrepreneurship is a crucial enterprise responsible for driving innovation and economic growth, and increasing the representation of women, especially in STEM and medical (STEMM) industries, is critical to ensuring the nation's overall health, economic well-being, and global competitiveness. On June 21-22, 2021, the National Academies of Sciences, Engineering, and held a virtual workshop to explore the current structural barriers (i.e., policies, practices, or other norms that systematically perpetuate gender disparities) driving the underrepresentation of women entrepreneurs across STEMM industries and strategies to overcome these barriers. Participants included representatives from a variety of sectors, including higher education, government, nonprofits, and industry, as well as researchers, evaluators, inventors, mentors, consultants, and policy analysts, among others. This publication highlights the presentation and discussion of the workshop.
Keywords: Industry and Labor

Diversity, Equity, and Inclusion in Chemistry and Chemical Engineering: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
A diverse workforce and inclusive workspaces are important components of future chemical and chemical engineering research. The workshop Diversity, Equity, and Inclusion in Chemistry and Chemical Engineering, held virtually on May 25-26, 2021, by the Chemical Sciences Roundtable, provided a venue for the chemical sciences community to discuss ideas and best practices for creating more diverse, equitable, and inclusive environments. Specifically, the workshop (1) explored barriers to diversity, equity, and inclusion (DEI) that are specific to chemistry and chemical engineering, (2) examined successful programs and best practices for increasing DEI in these fields, and (3) explored innovative approaches to create a culture in which all have equal opportunities to participate and advance. Ultimately, the workshop provided a forum for academic, government, and industrial participants to increase awareness of potential barriers to DEI and gain information needed to create more diverse, equitable, and inclusive environments in their workplaces. This document summarizes the presentations and discussions that took place during the workshop.
Keywords: Industry and Labor

The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The spring of 2020 marked a change in how almost everyone conducted their personal and professional lives, both within science, technology, engineering, mathematics, and medicine (STEMM) and beyond. The COVID-19 pandemic disrupted global scientific conferences and individual laboratories and required people to find space in their homes from which to work. It blurred the boundaries between work and non-work, infusing ambiguity into everyday activities. While adaptations that allowed people to connect became more common, the evidence available at the end of 2020 suggests that the disruptions caused by the COVID-19 pandemic endangered the engagement, experience, and retention of women in academic STEMM, and may roll back some of the achievement gains made by women in the academy to date. The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine identifies, names, and documents how the COVID-19 pandemic disrupted the careers of women in academic STEMM during the initial 9-month period since March 2020 and considers how these disruptions - both positive and negative - might shape future progress for women. This publication builds on the 2020 report Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine to develop a comprehensive understanding of the nuanced ways these disruptions have manifested. The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine will inform the academic community as it emerges from the pandemic to mitigate any long-term negative consequences for the continued advancement of women in the academic STEMM workforce and build on the adaptations and opportunities that have emerged.
Keywords: Policy for Science and Technology

Racial Justice, Diversity, Equity, and Inclusion in Neuroscience Training: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The Action Collaborative on Neuroscience Training: Developing a Nimble and Versatile Workforce (Action Collaborative) is an ad hoc activity convened under the auspices of the Forum on Neuroscience and Nervous System Disorders (Neuroscience Forum) of the National Academies of Sciences, Engineering, and Medicine. Originated from and informed by the work of the Action Collaborative, the Neuroscience Forum launched a virtual workshop series in order to explore the rapidly evolving neuroscience career landscape and how neuroscience training programs can help trainees to develop the knowledge and skillset needed to advance their careers and biomedical science. The first of these workshops, held on August 20, 2020, tackled complex issues related to racial justice, diversity, equity, and inclusion. Panel presentations of the workshop were envisioned as a starting point for an ongoing discussion around the ways scientists can stand against racism and support diversity, equity, and inclusion in neuroscience and academia, both in their local communities and in the broader world. This publication highlights the presentations and discussion of the workshop.
Keywords: Health and Medicine

Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors: Proceedings of a Symposium–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Careers in science, engineering, and medicine offer opportunities to advance knowledge, contribute to the well-being of communities, and support the security, prosperity, and health of the United States. Many women do not pursue or persist in these careers, or advance to leadership positions - not because they lack the talent or aspirations, but because they face barriers, including implicit and explicit bias; sexual harassment; unequal access to funding and resources; pay inequity; and higher teaching and advising load, among others. A 2020 report by the National Academies of Sciences, Engineering, and Medicine (the National Academies), Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors, reviews the current state of knowledge of factors that drive underrepresentation of women in science, technology, engineering, mathematics, and medicine (STEMM) and provides an overview of existing research on policies, practices, programs, and interventions for improving the representation of women in these fields. On March 19, 2020, the National Academies held a virtual symposium to share key messages and findings from the report as well as hear from experts on the range of issues addressed in the study. This publication highlights the presentation and discussion of that event.
Keywords: Policy for Science and Technology

Minority Serving Institutions: America's Underutilized Resource for Strengthening the STEM Workforce - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
There are over 20 million young people of color in the United States whose representation in STEM education pathways and in the STEM workforce is still far below their numbers in the general population. Their participation could help re-establish the United States' preeminence in STEM innovation and productivity, while also increasing the number of well-educated STEM workers. There are nearly 700 minority-serving institutions (MSIs) that provide pathways to STEM educational success and workforce readiness for millions of students of color—and do so in a mission-driven and intentional manner. They vary substantially in their origins, missions, student demographics, and levels of institutional selectivity. But in general, their service to the nation provides a gateway to higher education and the workforce, particularly for underrepresented students of color and those from low-income and first-generation to college backgrounds. The challenge for the nation is how to capitalize on the unique strengths and attributes of these institutions and to equip them with the resources, exceptional faculty talent, and vital infrastructure needed to educate and train an increasingly critical portion of current and future generations of scientists, engineers, and health professionals. Minority Serving Institutions examines the nation's MSIs and identifies promising programs and effective strategies that have the highest potential return on investment for the nation by increasing the quantity and quality MSI STEM graduates. This study also provides critical information and perspective about the importance of MSIs to other stakeholders in the nation's system of higher education and the organizations that support them.
Keywords: Education; Industry and Labor; Policy for Science and Technology

Expanding Underrepresented Minority Participation: America's Science and Technology Talent at the Crossroads - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 2011)
In order for the United States to maintain the global leadership and competitiveness in science and technology that are critical to achieving national goals, we must invest in research, encourage innovation, and grow a strong and talented science and technology workforce. Expanding Underrepresented Minority Participation explores the role of diversity in the science, technology, engineering and mathematics (STEM) workforce and its value in keeping America innovative and competitive. According to the book, the U.S. labor market is projected to grow faster in science and engineering than in any other sector in the coming years, making minority participation in STEM education at all levels a national priority. Expanding Underrepresented Minority Participation analyzes the rate of change and the challenges the nation currently faces in developing a strong and diverse workforce. Although minorities are the fastest growing segment of the population, they are underrepresented in the fields of science and engineering. Historically, there has been a strong connection between increasing educational attainment in the United States and the growth in and global leadership of the economy. Expanding Underrepresented Minority Participation suggests that the federal government, industry, and post-secondary institutions work collaboratively with K-12 schools and school systems to increase minority access to and demand for post-secondary STEM education and technical training. The book also identifies best practices and offers a comprehensive road map for increasing involvement of underrepresented minorities and improving the quality of their education. It offers recommendations that focus on academic and social support, institutional roles, teacher preparation, affordability and program development.
Keywords: Education; Policy for Science and Technology; Engineering and Technology; Math, Chemistry, and Physics; Industry and Labor

Seeking Solutions: Maximizing American Talent by Advancing Women of Color in Academia: Summary of a Conference - National Research Council (The National Academies Press, 2013)
Seeking Solutions: Maximizing American Talent by Advancing Women of Color in Academia is the summary of a 2013 conference convened by the Committee on Women in Science, Engineering and Medicine of the National Research Council to discuss the current status of women of color in academia and explore the challenges and successful initiatives for creating the institutional changes required to increase representation of women of color at all levels of the academic workforce. While the number of women, including minority women, pursuing higher education in science, engineering and medicine has grown, the number of minority women faculty in all institutions of higher education has remained small and has grown less rapidly than the numbers of nonminority women or minority men. Seeking Solutions reviews the existing research on education and academic career patterns for minority women in science, engineering, and medicine to enhance understanding of the barriers and challenges to the full participation of all minority women in STEM disciplines and academic careers. Additionally, this report identifies reliable and credible data source and data gaps, as well as key aspects of exemplary policies and programs that are effective in enhancing minority women's participation in faculty ranks. Success in academia is predicated on many factors and is not solely a function of talent. Seeking Solutions elucidates those other factors and highlights ways that institutions and the individuals working there can take action to create institutional cultures hospitable to people of any gender, race, and ethnicity.
Keywords: Policy for Science and Technology

Sexual Harassment of Women: Climate, Culture, and Consequences in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Over the last few decades, research, activity, and funding has been devoted to improving the recruitment, retention, and advancement of women in the fields of science, engineering, and medicine. In recent years the diversity of those participating in these fields, particularly the participation of women, has improved and there are significantly more women entering careers and studying science, engineering, and medicine than ever before. However, as women increasingly enter these fields they face biases and barriers and it is not surprising that sexual harassment is one of these barriers. Over thirty years the incidence of sexual harassment in different industries has held steady, yet now more women are in the workforce and in academia, and in the fields of science, engineering, and medicine (as students and faculty) and so more women are experiencing sexual harassment as they work and learn. Over the last several years, revelations of the sexual harassment experienced by women in the workplace and in academic settings have raised urgent questions about the specific impact of this discriminatory behavior on women and the extent to which it is limiting their careers. Sexual Harassment of Women explores the influence of sexual harassment in academia on the career advancement of women in the scientific, technical, and medical workforce. This report reviews the research on the extent to which women in the fields of science, engineering, and medicine are victimized by sexual harassment and examines the existing information on the extent to which sexual harassment in academia negatively impacts the recruitment, retention, and advancement of women pursuing scientific, engineering, technical, and medical careers. It also identifies and analyzes the policies, strategies and practices that have been the most successful in preventing and addressing sexual harassment in these settings.
Keywords: Policy for Science and Technology; Behavioral and Social Sciences

Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine: Opening Doors - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Careers in science, engineering, and medicine offer opportunities to advance knowledge, contribute to the well-being of communities, and support the security, prosperity, and health of the United States. But many women do not pursue or persist in these careers, or advance to leadership positions - not because they lack the talent or aspirations, but because they face barriers, including: implicit and explicit bias; sexual harassment; unequal access to funding and resources; pay inequity; higher teaching and advising loads; and fewer speaking invitations, among others. There are consequences from this underrepresentation of women for the nation as well: a labor shortage in many science, engineering, and medical professions that cannot be filled unless institutions and organizations recruit from a broad and diverse talent pool; lost opportunities for innovation and economic gain; and lost talent as a result of discrimination, unconscious bias, and sexual harassment. Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine reviews and synthesizes existing research on policies, practices, programs, and other interventions for improving the recruitment, retention, and sustained advancement into leadership roles of women in these disciplines. This report makes actionable recommendations to leverage change and drive swift, coordinated improvements to the systems of education, research, and employment in order to improve both the representation and leadership of women.
Keywords: Policy for Science and Technology

Action Collaborative on Preventing Sexual Harassment in Higher Education: Year Two Annual Report of Activities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Action Collaborative's Year 2 Annual Report summarizes the Action Collaborative's collective progress in the 2020-2021 year, identifies areas for future focus, discusses trends in organizations' reported areas of work, and highlights work shared by member organizations and partner network organizations. A complete collection of "descriptions of work" authored by member and partner network organizations is available in the repository.
Keywords: Education

Defense Research Capacity at Historically Black Colleges and Universities and Other Minority Institutions: Transitioning from Good Intentions to Measurable Outcomes - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Historically Black Colleges and Universities (HBCUs) and other minority institutions (MIs) represent a valuable resource to expand the Department of Defense's (DoD) government and extramural workforce and science and technology enterprise. The more than 400 public and private HBCUs, Tribal Colleges and Universities, Hispanic-Serving Institutions, and other two- and four-year MIs are positioned to make strong and uniquely important contributions to the defense research enterprise, offering DoD an opportunity to widen its talent pool and diversify STEM research and ultimately strengthen its ability to support national security. Defense Research Capacity at Historically Black Colleges and Universities and Other Minority Institutions examines the status of DoD research at HBCUs and MIs, including the methods and means necessary to advance research capacity at these institutions in order to comprehensively address the national security and defense needs of the United States. This report offers recommendations to guide DoD, Congress, HBCU/MIs, and partnering entities in supporting and strengthening the role of these institutions in defense research. A strategic commitment will translate into increased opportunities for HBCU/MIs to diversify the future American academic, industrial, and government STEM workforce upon which DoD will depend.
Keywords: Education